Cultural geography: a survey of perceptions held by Cultural Geography Specialty Group members - Smith, Jeffrey S. (My University, 2001)
As of the year 2000, the Cultural Geography Specialty Group of the Association of American Geographers had 465 members and ranked fourth overall in total membership within the association. Furthermore, cultural geographers had the second fastest growing specialty group between 1993 and 1998, after the Geographic Perspectives on Women specialty group. In spite of this demonstrated overwhelming appeal among geographers, to date, no one has systematically analyzed the subdiscipline of cultural geography to determine such things as its links to other aspects of the discipline, its major scholarly contributions, its most highly regarded publication outlets, its notable practitioners, and its most recognized departments. As the ranks of cultural geographers have swelled, the subdiscipline has become multifaceted. This article contextualizes and interprets the results of a survey sent to members of the 1998–1999 Cultural Geography Specialty Group. Outcomes include Louisiana State University and the University of Texas at Austin listed as offering the strongest cultural geography departments, Wilbur Zelinsky being deemed the subfield's most outstanding living practitioner, and the Annals of the Association of American Geographers named the journal that best meets cultural geographers’ needs.
Keywords: Cultural geography; Strongest departments; Distinguished scholars; Publication outlets